Compressible Metalized Soft Magnetic Sponges with Tailorable Electrical and Magnetic Properties. Issue 2 (13th January 2020) - Yan, Xiaorong; Hu, Mingjun; Liu, Jinxing; Yan, Li; Zhang, Naibai; Gao, Jiefeng; Liu, Jinzhang; Shan, Guangcun; Yang, Jun
Abstract: Porous metallic sponge has shown enormous application potential in many fields including electrochemical electrode, catalysis, sensors, separation and purification, microwave and sound inhibition, etc. In this paper, we described the preparation of a class of highly compressible Ni−Co alloy‐based sponges with tailorable conductivity and soft magnetic properties as well as EMI shielding ability by employing elastic porous melamine sponge as the support. The melamine sponge was first modified by one‐step dopamine‐triggered radical polymerization reaction, in which polymer brushes with quaternary ammonium cations were grafted onto the sponge fibers for the capture of negative catalyst moieties. The immobilized catalyst moieties could subsequently induce in‐situ chemical deposition of a uniform and well‐adhesive Ni−Co alloy layer with controllable compositions and thickness on the fiber surface owing to the interpenetrating network between hydrophilic polymer brushes and the in‐situ deposited metal layer. The obtained alloy sponges show good compression‐resilience property, excellent conductivity and favorable soft magnetic performance as well as good compressive fatigue resistance during repeated compression‐release cycles, and thus can find promising applications in many fields, including pressure resistance sensors, magnetic controlled pollutant absorbents, tunable EMI shielding materials, etc. Abstract : A class of highly compressible Ni−Co alloy‐based sponges with tailorable conductivity and soft magnetic properties was prepared by employing elastic porous melamine sponges that was modified through dopamine‐induced free radical polymerization reactions as the support. The obtained alloy sponges show good compression‐resilience behavior, excellent soft magnetic properties (54 emu/g) and high electromagnetic interference shielding effectiveness (7273 dB ⋅ cm 2 ⋅ g −1 ), and thus can find promising applications in wide fields including pressure resistance sensors, magnetic absorbents, tunable EMI shielding, etc.